Comprehensive Review of Advanced Multi-Pulse Rectifier Technology and Its Application in Electric Vehicle Fast Charging Systems - Harahap, Partaonan; Hamid, Muhammad Imran; Hazmi, Ariadi (LPPM Universitas Andalas, 2025)
Fast charging technology for electric vehicles (EVs) is one of the key components in supporting the transition to a sustainable transportation system. This article discusses advanced multi-pulse rectifier technology, such as 12-pulse, 24-pulse, and 48-pulse configurations, which are used to improve power efficiency and reduce harmonic distortion. The analysis includes the working principles, benefits compared to conventional rectifier technology, and the challenges of its implementation. The review results show that multi-pulse rectifiers significantly reduce Total Harmonic Distortion (THD), improve power quality, and facilitate integration with renewable energy sources. This article also suggests future research directions to address the limitations of current technology and to encourage further innovations in efficient and environmentally friendly EV charging.